Helicobacter pylori Eradication Therapy: Current Availabilities. (27th June 2012) - Gasparetto, M.; Pescarin, M.; Guariso, G.
Abstract : Background . Though Helicobacter pylori (HP) infections have progressively declined throughout most of the industrialized countries, a gradual increase in failure of HP eradication treatments is observed. Aim . To critically review evidence on the efficacy of the therapeutic availabilities for HP eradication, as yet. Methods . A selection of Clinical Trials, Systematic Reviews and Meta-analyses within the time period 2010–2012, was performed through a Medline search. Previous references were included when basically supporting the first selection. Results . An increasing rise in HP resistance rates for antimicrobial agents is currently observed. Further causes of HP treatment failure include polymorphisms of the CYP 2C19, an increased body mass index (BMI), smoking, poor compliance and re-infections. Alternative recent approaches to standard triple therapy have been attempted to increase the eradication rate, including bismuth-containing quadruple therapy, non-bismuth containing quadruple therapy, sequential therapy and levofloxacin-containing regimens. Conclusions . The main current aims should be the maintenance of a high eradication rate (>85%) of HP and the prevention of any increase in antimicrobial resistance. In the next future, the perspective of a tailored therapy could optimize eradication regimens within the different countries.